The impact of ICT and intangible capital accumulation on labour demand growth and functional income shares - Robert Stehrer (The Vienna Institute for International Economic Studies (wiiw), 2022)
This paper investigates whether the diffusion of tangible IT and CT capital and intangible capital asset types has an impact on labour demand growth and the share of labour income in total income at the industry and country level. The econometric analysis is derived from a Cobb-Douglas production function taking empirical stylized facts into account. The effects of technical progress embodied in the various forms of capital impact along inter-industry and intercountry production linkages, which are considered by using global value chain indicators. The analysis is broken down to examine the influence on different types of labour, including the dimensions of gender, age, and educational attainment. Accumulation of ICT assets have generally insignificant and in some cases small positive effects on labour demand and income shares, though patterns differ across types of labour. Intangible assets show a positive relation with respect to labour demand growth.
Keywords: J23; J31; O33; O52; 330; capital accumulation; ICT capital; intangibles; labour demand; income distribution